Strengthening records management in higher education: A case of University Library practices in the Philippines - Palcullo, Vince Ervin V.; Seelakate, Pimphot (Record and Library Journal, 2025)
Background of the study: The University Libraries is an academic library from University A, one of the oldest private universities or Higher Education Institutions in the Philippines, located in the Western Visayas region. It collects and preserves the organizational memory and evidence by keeping university records. Purpose: This research aims to examine the records management program at a specific university library in the Philippines that adheres to ISO 9001:2015 – Quality Management Systems. This highlights the importance of preserving records in university libraries to guarantee that the library’s activities are adequately documented for historical, administrative, archival, and legal purposes. Method: This qualitative research uses a literature review and observation to gather an in-depth understanding of a case study of the university library, and uses the records life cycle and PEST analysis as a framework to examine the case. Findings: Although the University Library adheres to ISO 9001:2015, the research shows that examining its background, applying PEST analysis to its environment, and analyzing its functions and organizational culture help researchers identify the current challenges it faces and inform the development of its records management program. Conclusion: It is critical for the University to successfully establish an effective records management system as this will positively impact all departments and offices, particularly the University Library. Therefore, developing a records management manual would greatly benefit the organization as a whole. This manual should include policies and procedures and define the roles and responsibilities of those involved.